Potentiometric determination of the dissociation constants of epirubicin HCl and irinotecan HCl - (:unkn) unknown (ELSEVIER SCIENCE BV, 2006)
Dissociation constants and relative abundances of ionised and non-ionised forms of epirubicin HCl and irinotecan HCl were determined potentiometrically.
Keywords: COMPATIBILITY; STABILITY; DRUGS